Obesity Paradox of All-Cause Mortality in 4, 133 Patients Treated with Coronary Revascularization. (18th November 2021) - Li, Chengzhuo; Han, Didi; Xu, Fengshuo; Zheng, Shuai; Zhang, Luming; Wang, Zichen; Yang, Rui; Yin, Haiyan; Lyu, Jun
Abstract : Objectives . The purpose of this study was to determine whether there is a dose-response relationship between body mass index (BMI) and all-cause mortality in patients after coronary revascularization. Methods . The MIMIC-III database (version 1.4) was used as the sample population. For variables with less than 10% of values missing, we used the mice package of R software for multiple imputations. Cox regression was used to determine the risk factors of all-cause mortality in patients. RCSs were used to observe the relationship between BMI and all-cause mortality. Additional subgroup and sensitivity analyses were also performed to explore whether the conclusion can be applied to specific groups. Results . Both univariate and multivariate Cox models indicated that the mortality risk was lower for overweight patients than for normal-weight patients (P < 0.05 ). In RCS models, BMI had a U-shaped relationship with all-cause mortality of patients after coronary artery bypass grafting (CABG) (P for nonlinearity = 0.0028). There was a weak U-shaped relationship between BMI and all-cause mortality after percutaneous coronary intervention (PCI), but the nonlinear relationship between these two parameters was not significant (P for nonlinearity = 0.1756). Conclusions . The obesity paradox does exist in patients treated with CABG and PCI. RCS analysis indicated that there was a U -shaped relationship between BMI and all-cause mortality in patients after CABG. After sex stratification, the relationship between BMI and all-cause mortality in male patients who received PCI was L -shaped, while the nonlinear relationship among females was not significant.